2004
DOI: 10.1007/s10071-004-0242-y
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behaviour in domestic pigs (Sus scrofa): remembering and prioritizing food sites of different value

Abstract: This experiment investigated whether domestic pigs can remember the locations of food sites of different relative value, and how a restricted retrieval choice affects their foraging behaviour. Nine juvenile female pigs were trained to relocate two food sites out of a possible eight in a spatial memory task. The two baited sites contained different amounts of food and an obstacle was added to the smaller amount to increase handling time. On each trial, a pig searched for the two baited sites (search visit). Onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 20 publications
0
35
0
2
Order By: Relevance
“…Wild boars and feral pigs forage in large home ranges in which they can exploit an enormous variety of food sources (Gundlach 1986;Schley and Roper 2003). Under such conditions, individuals would beneWt from good spatial memory skills and a high Xexibility in behaviour (Held et al 2005). Indeed, studies on cognitive abilities in domestic pigs have demonstrated good spatial memory skills (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Wild boars and feral pigs forage in large home ranges in which they can exploit an enormous variety of food sources (Gundlach 1986;Schley and Roper 2003). Under such conditions, individuals would beneWt from good spatial memory skills and a high Xexibility in behaviour (Held et al 2005). Indeed, studies on cognitive abilities in domestic pigs have demonstrated good spatial memory skills (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to rats, pigs naturally tend to explore novel aspects of their environment (Wood-Gush & Vestergaard, 1991). Pigs also have good spatial memory abilities and they are able to learn tasks quickly (e.g., Croney, 1999;Held et al, 2002;Held et al, 2005;Puppe et al, 2007; reviewed in Gieling et al, 2011). As well, wild and feral pigs have a life history in which memory is valuable; particularly because they live socially, have large foraging ranges, and have foraging habits/movement patterns/nesting sites that change with season and food availability (Graves, 1984).…”
Section: Novel Object Recognition Taskmentioning
confidence: 99%
“…For both I and NI pigs, revisits to buckets were assessed as a measure of impaired working memory (van der Staay et al, 2012). Pairs of I/NI pigs proceeded to phase 2 when the I pig reached the criterion of visiting a maximum of 2 unbaited buckets during the relocation visits in at least 6 out of 8 consecutive trials (Held et al, 2005;Held et al, 2010).…”
Section: Ift Phase 1 -Individual Trainingmentioning
confidence: 99%
“…Alternatively, non-informed MS pigs may have adopted a scrounger role -where the submissive pig is exploitedonly if more profitable bait could be obtained. The social organisation of wild boar is characterised by cooperation, rather than competition (Focardi et al, 2015), and domestic pigs can alter their foraging behaviour in response to the quantity of bait that can be retrieved (Held et al, 2005).…”
Section: Ift Phasementioning
confidence: 99%
See 1 more Smart Citation